Problematik Guru Bahasa Indonesia Berkomunikasi secara Efektif, Empatik, dan Santun dengan Peserta Didik - Yusuf, Yusron (Institute Agama Islam Al-Qolam Malang, 2019)
Effective communication in learning is a process of transforming messages in the form of science and technology from educators to learners. Learners are able to understand the purpose of the message in accordance with the intended purpose. Thus, adding insight into science and technology and causing behavior change for the better. The teacher is the party most responsible for the ongoing effective communication in learning. A teacher as a teacher is required to have good communication skills in order to produce an effective learning process. Effective problematic communication, empathy, and politeness to learners include: 1) anxiety speaking in front of the class and 2) saying dirty to students. Solution of effective communication problems empathic, and courteous to learners include: 1) positive thinking and 2) improvement of teacher quality and professionalism.